Changes in children’s time use during periods of financial hardship - Arnup, Jessica L; Black, Nicole; Johnston, David W (My University, 2021)
Economically disadvantaged children are more likely than other children to experience worse cognitive, health, and behavioral outcomes. The mechanisms for these associations are not fully understood, hindering policy initiatives aimed at closing the gaps. One hypothesis is that children experiencing financial hardship allocate their time differently. In this study, we use seven waves of time use diary data from a large sample of Australian children to explore how children’s time use changes when their family experiences financial hardship or deprivation. Focusing on four key child health and development time inputs––screen time, physical activity, sleep, and reading––we find that financial hardship is associated with significantly more screen time, particularly passive screen time, and screen time at excessive levels. We explore potential mechanisms for these associations.
Journal of Population Economics
Keywords: Adolescents and youth; Families and relationships; Income, wealth and finances; Lifestyle